Assessing Oral Cancer Awareness Among Dentists - NAMDAR PEKİNER, FİLİZ MEDİHA (SPRINGER, 2018)
The aim of this study was to assess oral cancer awareness among dentists who attended 101st FDI World Dental Congress, stanbul, Turkey. Among 170 dentists who agreed to participate, there were 13 oral surgeons, 6 restorative dentists, 4 endodontists, 4 orthodontists, 6 periodontists, 5 pedodontists, and 14 prosthodontists. Knowledge of oral cancer risk factors and diagnosis procedures, dentists' attitude towards oral cancers, management practice regarding oral cancer, and oral cancer information sources were assessed using 25 questions. The data were analyzed with IBM SPSS Statistics 22.0 program. Among 170 participant dentists, there were 69 (40.6%) male dentists and 101 (59.4%) female dentists. Largest number of them identified tobacco (98.8%) and alcohol usage (91.2%), prior oral cancer lesions (95.3%), viral infections (90.0%), UV exposure (86.5%), and betel quid chewing (80.6%), and lower numbers reported older age (56.5%) and low consumption of fruit and vegetables (52.4%). Oral medicine specialists scored marginally higher in indicating erythroplakia and leukoplakia most likely to be precancerous and squamous cell carcinoma as the most common form of oral cancer (p<0.01). This study highlighted the importance of improved educational methods for dentists on oral cancer detection and prevention.
Keywords: Oral cancer; Awareness; Dentist; SQUAMOUS-CELL CARCINOMA; GENERAL DENTISTS; RISK-FACTORS; KNOWLEDGE; OPINIONS; CAVITY; PREVENTION; ATTITUDES; ALCOHOL; PROFILE